O impacto do ensino superior no desenvolvimento econômico dos municípios brasileiros: uma análise comparativa - Silva, Kassyo Modesto da (2023)
This work used the human capital theory as a theoretical basis to assess the economic impact of the expansion of Higher Education Institutions (HEIs) in smaller cities in Brazil, more specifically, those that did not yet have an HEI. Using data from INEP and IBGE, the study applied the staggered differences-in-differences technique to compare municipalities that received the first HEI with those that did not over several periods. The results showed that the arrival of an HEI in a previously unserved municipality had a growing positive impact on the region's economic growth, reaching 15.2% after 13 years of intervention. It was concluded that the expansion of HEIs in smaller cities brings significant economic benefits in the long term.